Individual profiles of psychological suitability for police service (according to the results of the individual typological questionnaire) - V. I. Barko; V. V. Barko; O. O. Yevdokimova (Bulletin of Kharkiv National University of Internal Affairs)
The individual psychological profiles of police officers, obtained through a long-term study using the adapted Ukrainian-language psychodiagnostic methodology “Individual Typological Questionnaire” by L. Sobchyk, have been studied and analysed. The presented results contain a description of different types of individual personality profiles, which are characterised as favourable, less favourable and unfavourable for the service activity in the National Police of Ukraine depending on typological features, specificity of leading tendencies, thinking and communication properties, type of reaction to stress, etc. These typical psychological profiles include fifteen variants, the study of which will help the psychologists of the National Police psychological support units to formulate scientifically sound forecasts of the success of the candidates for police officers during the psychological stage of professional selection, as well as to help police officers in conducting competitions for vacant positions, carrying out the certification procedure, etc.